Innovation, competition and technical efficiency - Elina Berghäll (Cogent Business & Management, 2016)
Contradictory empirical and theoretical evidence on the relationship between innovation and competition has been reconciled in a model that yields an inverted U-shaped curve. I test whether the predictions of the model are supported by the data with an unbalanced panel of firms for 1990–2003 in a high productivity growth, high-tech industry, Finnish ICT manufacturing. In particular, I investigate how well alternative, yet rigorous measures of innovation and the technology gap, such as R&D intensity, R&D elasticity, technical change, technical efficiency and total factor productivity fare with respect to competition measured by the Lerner index. The results prove sensitive to the choice of variable. Overall, the model is not supported by the empirical evidence of the industry.
Keywords: 650